Educating by delighting. Three Chilean children’s magazines in the first decades of the 20th century: El Peneca, Mamita and El Abuelito - Clemente San Román, Yolanda (Revista General de Información y Documentación, 2023)
From the mid-19th Century and throughout the 20th Century, children’s magazines in Chile served as an instrument of entertainment and education for the country’s children. Titles such as El Peneca, Mamita and El Abuelito are clear examples of this. Through their pages, which contain tales, short stories, games and quizzes of all kinds, children are instructed in the canons of a strong Catholic morality, love of their country, respect for established rules and obedience to their elders. An analysis of the contents of these publications reveals the patterns of behaviour imposed by an orthodox society on a young public which must be indoctrinated with a certain ideology, since they are going to be the future of the nation.